Three Wives of Political Prisoners Write about Indonesias New Order Military Regime - Alkatiri, Zeffry (ASPENSI in Bandung, Indonesia, 2012)
ABSTRACT: This article examines three books from three women writers who were the wives of three political prisoners in Indonesia. They tell us on their life stories in Indonesia where their husbands were incarcerated by the New Order regime (1966-1998). The regime even held one of the women prisoners as well. This article sees also how they revealed their life experiences, though coming from different periods of time, using the same sarcastic criticism point of view. The aim of this article is to show the differences and similarities of the writers views towards the brutality of the military regime during the New Order era. The research uses a discourse analysis by looking at the revealment structures from the three writers through a historical perspective. Another aspect revealed by the three wives of the political prisoners is that the people of Indonesia themselves were forced to accept all kinds of political pressures from the Old Order regime, and even more from the New Order regime who ruled longer. The three books have indirectly presented a historical reflection on the gloomy process of a nations journey: what was Indonesia during the New Order military regime.KEY WORDS: Wives of political prisoners, military regime, New Order government, and three books.About the Author: Dr. Zeffry Alkatiri is a Lecturer at the Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok, West Java, Indonesia. He can be reached at: zeffry_al@yahoo.comHow to cite this article? Alkatiri, Zeffry. (2012). âThree Wives of Political Prisoners Write about Indonesias New Order Military Regimeâ in TAWARIKH: International Journal for Historical Studies, Vol.3(2) April, pp.235-252. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 27, 2012); Revised (March 30, 2012); and Published (April 28, 2012).